Digitalization of mass media as a factor of influence on trust in artificial intelligence - P. V. Razov; A. V. Garaganov (Цифровая социология)
The article discusses the influence of media digitalization on the individuals’ trust in artificial intelligence technologies. The authors study the key features associated with the current state of the media market, as well as highlight the risks that affect the development of the media and consumer confidence in them. An important place in this work is given to the analysis of the media digitalization. The main elements that reflect the consequences of this process are described, as well as global trends associated with the mass media market. In this paper, the aspect of individuals’ trust in artificial intelligence is studied, in particular, the main reasons for distrust in the phenomenon under study are considered. The authors have identified the relationship between the process of digitalization of the media and the trust of individuals in artificial intelligence. In the final part of the article, the authors present the results of digitalization of the media in the context of the transition to new formats, and also reveal the existing mechanism of the impact of this transition on people’s trust in artificial intelligence.